Synergistic seizure reduction in patient with persistently elevated N-desmethylclobazam levels, CYP450 genetic polymorphism, and responsive neurostimulator targeting centromedian nuclei of bilateral thalami - Andrew Zillgitt; David E Burdette; Atheel Yako; Revati Rashingkar; Ashleigh Terrell; Sydney Jacobs; Michael D Staudt (Epilepsy & Behavior Reports)
Clobazam (CLB) and cenobamate (CNB) are commonly used antiseizure medications (ASMs) in the treatment of patients with drug-resistant epilepsy (DRE). However, concomitant use of these two ASMs may lead to significant treatment-related adverse events (TRAE). Furthermore, these TRAE may be exacerbated in individuals with genetic polymorphisms involving the P450 system. In patients with DRE, epilepsy surgery, including neuromodulation, may lead to improved seizure control and a reduction in systemic TRAE from ASMs. This case report describes a patient with drug-resistant idiopathic generalized epilepsy (IGE) who experienced persistent excessive somnolence correlated with elevated N-desmethylclobazam (N-CLB) levels. Pharmacogenetic testing revealed poor metabolism of CYP2C19, and N-CLB levels remained elevated and detectable for nearly one year after the discontinuation of treatment with CLB and CNB. Responsive neurostimulator (RNS) implantation within the bilateral centromedian nuclei (CMN) of the thalamus resulted in seizure freedom until N-CLB levels fell, after which there was an 83–93 % reduction in the frequency of generalized tonic-clonic seizures (GTC).